Transcriptional and translational analyses of the UL2 gene of equine herpesvirus 1: a homolog of UL55 of herpes simplex virus type 1 that is maintained in the genome of defective interfering particles. - Harty, R N (1993)
Defective interfering particles (DIPs) of equine herpesvirus 1 (EHV-1; Kentucky A strain) mediate persistent infection. DNA sequences at the L terminus, which contain the UL2 gene (homolog of UL55 of herpes simplex virus type 1 and open reading frame 3 of varicella-zoster virus) of standard EHV-1, have been shown to be highly conserved in all clones of the EHV-1 DIP genome. The UL2 mRNA was characterized by S1 nuclease analyses, which mapped the 5' and 3' termini of the 0.9-kb early UL2 mRNA to approximately 26 and 16 nucleotides downstream of a TTTAAA box and polyadenylation signal, respectively. The UL2 open reading frame, present within both the EHV-1 standard and DIP genomes, was inserted into the transcription expression vector pGEM-3Z to yield constructs pGEML2 and pDIL2, respectively. After in vitro transcription and translation, both constructs yielded a comigrating 23-kDa protein, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Polyclonal antiserum was raised against the UL2 protein by injecting rabbits with a TrpE/UL2 fusion protein expressed from plasmid pATH23L2 in Escherichia coli. The UL2-specific antiserum reacted in Western immunoblot and immunoprecipitation analyses with a 23-kDa polypeptide synthesized in cells infected with standard EHV-1 or DIP-enriched virus. These data also indicated that the UL2 polypeptide was more abundant in DIP-infected cells than in standard EHV-1-infected cells. Results from time course and pulse-chase analyses suggested that the UL2 polypeptide has a rapid turnover rate in DIP-infected cells.